FEATURES MORPHOFUNCTIONAL STATE OF THE CELLULAR ELEMENTS OF PERIODONTAL TEETH AFTER THEIR PREPARATION - Цветкова, Н.В. (World of Medicine and Biology, 2015)
The aim of the rese arch wasto study themor phofunctional condition of periodontal cells teeth that have beenun derpreparation fixedconstructions of prostheses. Fibroblast activity compared to the previous period continued to rise, as evidenced by the increase in basophilia nucleoli and cytoplasm (cell placed columns). In blood vessels pulp mononuclear cells present, but they periodontal vessels revealed, indicating a slow inflammatory response, increased limfoidna emigration, there are few plasma. Processes many fibroblasts show basophilia. Tsementoblasty oval are on the side of the mesial buccal root across the surface of cement, but it should be noted that distinguish young fibroblasts from tsementoblastiv difficult, and only their location provides an opportunity to resolve the issue. Osteoblasts are activated. On the mesial and lingual surfaces of the mesial root of the same type of change buccal surface, but the reactivity of cellular elements expressed less. At this level of the distal root inflammation similar to mezialnym root, but expressed to a lesser degree. In the fourth and fifth levels increase in the number of cellular elements near the wall alveoli and especially near the cement.In varying degrees, marked basophilia cellular elements. It is more intense in the cytoplasm of cells that are placed in the middle of periodontal gap, and less - near the cement where more rounded cells. Neighborhoods cement cells are a series of three - four-oriented perpendicular to the root. Close blood vessels are observed diffuse lymphocytes. After dissection of marginal periodontal fibroblasts premolars some clear boundaries are marked and well-stained nucleus. There are single cells Hofbauera. At the same time we were recorded active fibroblasts increased in size, with no clear boundaries between cells and the second element of the connective tissue. In some areas of marginal periodontal neutrophils are destroyed. This shift phases of the inflammatory process can be considered organ periodontal feature. In fact there are active periodontal fibroblasts, they increased in size. Basophiliafibroblasts increases. Leukocyte emigration expressed weaker things of six hours spent preparing the tooth.Conclusion. Swelling in the periodontium during noti dentical root devel opsin the art and arenot expresse dleuko cyte fibroblastic reaction, reduced response of the rcellelements and decreases "swelling" bone.
Keywords: preparation; mucous membrane; cellular elements